2009
DOI: 10.1667/rr1739
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Nephropathy is not Mitigated by Antagonists of Oxidative Stress

Abstract: Persistent, chronic oxidative injury may play a mechanistic role in late radiation injury. Thus antioxidants may be useful as mitigators of radiation injury. The antioxidants deferiprone, genistein and apocynin were tested in a rat radiation nephropathy model that uses single-fraction total-body irradiation (TBI) followed by syngeneic bone marrow transplant. Deferiprone was added to the drinking water at 1.0 or 2.5 g/liter, starting 3 days after the TBI. Urinary bleomycin-detectable iron, which could enhance p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 36 publications
3
16
1
Order By: Relevance
“…We also tested three anti-oxidant drugs as mitigators of radiation nephropathy in this model and found them ineffective [4]. Together with the present gene expression data, we conclude that there is no evidence for a role for chronic oxidative stress in radiation nephropathy.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…We also tested three anti-oxidant drugs as mitigators of radiation nephropathy in this model and found them ineffective [4]. Together with the present gene expression data, we conclude that there is no evidence for a role for chronic oxidative stress in radiation nephropathy.…”
Section: Discussionsupporting
confidence: 51%
“…Using an experimental radiation nephropathy model, we have not been able to confirm this hypothesis. Biochemical and histological markers of oxidative stress were absent after irradiation and anti-oxidants were ineffective in the mitigation of radiation nephropathy [24]. But it remained possible that the assays were not sensitive enough, and that the anti-oxidants chosen were not appropriate for the model.…”
Section: Introductionmentioning
confidence: 99%
“…We found neither genomic nor biochemical nor histochemical evidence for chronic oxidative stress [17,41]. We also tested deferiprone, genistein, and apocynin, which all have anti-oxidant activity, but none of these were mitigators of radiation nephropathy [31]. Despite previous evidence for deficient nitric oxide production in radiation nephropathy, post-irradiation use of nitrite was deleterious ( Table 2).…”
Section: Incidence Of Renal Failurementioning
confidence: 76%
“…Calveley et al [14] also demonstrated that genistein treatment could provide partial mitigation of the effects of lung irradiation as evidenced by an improvement in breathing rate and a delay of lethality. In contrast, genistein did not show any antifibrotic effects when given as a mitigator for late radiation-induced renal toxicities [70]. Limitations to the use of genistein include its rapid elimination from the circulation and a narrow time window for administration.…”
Section: • • Naturally Occurring Antioxidantsmentioning
confidence: 89%